Evaluation of low-temperature properties of mixtures of bitumen and SBS polymers of various topologies by the ABCD method - Nikolaevsky, Vladimir E.; Duzhiy, Pavel A.; Nebratenko, Dmitry Yu. (Vojnotehnički glasnik / Military Technical Courier, 2023)
Introduction: Due to climate change, scientists around the world, including specialists in the road construction industry, are forced to take into account the need for regular monitoring of the low-temperature properties of both individual building materials and the properties of multicomponent road composites based on them.  Therefore, the possibility of developing new approaches and methods for evaluating these properties is being studied. Methods: For these purposes, Dr. Kim Sang-Soo proposed a new method for evaluating the low-temperature properties of road binders, which was called the ABCD (Asphalt Binder Cracking Device) method. The use of the device does not require special skills and knowledge and auxiliary equipment is widely available in laboratories of road construction organizations. The duration of the test does not exceed 4-5 hours.Results: The possibility and effectiveness of regulating the cracking temperature of bitumen-containing binders by introducing styrene-butadiene thermoplastics of various topologies into the composition is shown using the example of industrially produced batches of petroleum road viscous oxidized bitumen and applying the ABCD methodology.Conclusions: In Russia, where winter temperatures in the vast majority of the country fall below minus 30 degrees Celsius, it is extremely important to control the behavior of bitumen binders and multicomponent mixtures of different compositions (asphalt concrete mixtures). The national standard GOST R 58400.11-2019 has been put into effect and the production of appropriate measuring equipment has been established. At the same time, the ABCD method can be used both to study the properties of mixtures of binders with polymers of various topologies and to select a commercial binder that meets the requirements of a specific region of highway operation.
Keywords: cracking temperature; polymer-modified bitumen; ABCD method; styrene-butadiene thermoplastics of various topologies